On Uplink and Downlink Packet Scheduling in Full-Duplex Wireless Mesh Networks - Wang, H.; Chin, K.; Soh, Sie Teng (IEEE Communications Society, 2015)
We study the problem of deriving the shortest schedule required to forward both uplink and downlink packets in wireless mesh networks (WMNs) with full duplex capability. We derive the theoretical upper and lower bound of the schedule, and propose a novel centralized algorithm, called UDMAC, that greedily generates a schedule on a path-by-path basis and ensures nodes have sufficient antennas for transmissions, receptions, and interference cancellation. Our results show that UDMAC outperforms a state-of-the-art half-duplex scheduling algorithm by at least 60% in terms of schedule length.